Blended Learning for Skill Development in EFL Teacher Preparation - Hasan, Hind Salah (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Blended learning, which integrates online and face-to-face instruction, is increasingly essential in teacher education, especially for English as a Foreign Language (EFL). Gap: Research is limited on its specific effectiveness in building EFL pedagogical skills. Aim: This study examines whether blended learning better supports teaching success for EFL prospective teachers than traditional methods. Results: Blended and face-to-face methods equally boost educational success, but the blended approach better prepares future teaching skills. Novelty: This study reveals blended learning's unique value in EFL teacher preparation. Implications: Institutions should adopt blended learning to enhance adaptive teaching skills for modern classrooms. Highlights: Blended learning enhances teaching skills by combining online and face-to-face methods. This approach uniquely prepares EFL teachers for modern, adaptive classrooms. Institutions should integrate blended models for effective teacher development. Keywords: Blended Learning, EFL Teacher Training, Pedagogical Skills, Educational Success, Hybrid Teaching